Assessment of Perceived Health Competencies among Nursing Students and its Correlation with Self-Esteem - A Multi Institutional Study - Musarat Nazir, Saeedullah, Muhammad Ilyas, Hayat Ali, Sardar Ali, Amir Sultan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Perceived health competency is a measure that predicts the behavior and outcome of individuals and enhances the self-confidence level of health care providers, while self-esteem is the skills and emotions that show the individual how to respect and not underestimate themselves. Aim: To determine the prevalence of perceived health competencies among nursing students and to investigate its relationship with self-esteem. Method: The study was conducted in the ten nursing institutes of Khyber Pukhtankhwa from December 2022 to February 2023. The design was cross-sectional analytical having sample size of 358 using sample random sampling method. The instruments used to assess perceived health competency were the perceived health competence scale (PHC) and the Rosenberg self-esteem questionnaire. Pearson correlation was used for association of self-esteem and perceived heath competencies. Results: Among the participants, the majority of the students were male (58.1%) compared to female students (41.9%). The level of perceived health competencies among majority (72%) nursing students was higher (72%). The level of self-esteem among majority (78%) of the participants was average. Furthermore, the findings revealed that health competency (behavior) were strongly associated with self-esteem (r = 0.089), while outcome was moderately correlated with self-esteem (r = 0.039). Conclusion: Nursing students health competencies (behavior) were higher among nursing students, which are strongly correlated with self-esteem, which will promote health-promoting behaviors among nurses. Furthermore, postgraduate students outclass other students in self-esteem and health competencies. Practical implication: Nursing students with low perceived health competence may be at risk of low self-esteem. Low self-esteem affects the health-promoting behaviors of students, which will affect their academic and clinical competencies and, in the long term, affect the quality of care and patient outcomes. Keywords: Self-esteem, health education, health behaviors, perceived health competencies, health promotion, nursing students